Kepemimpinan Visioner; dalam Membangun Budaya Organisasi Berprestasi di MAN 2 Probolinggo - Sugianto, Muhammad (LP3M Universitas Islam Zainul Hasan Genggong, 2018)
The birth of organizational culture in Islamic educational institutions can not be separated from the typology of visionary leadership. Organizations are therefore defined as a rational tool for coordinating and controlling a group of people in the process of achieving goals. Leadership appears in the process by which a person directs, guides, influences and or controls the thoughts, feelings and behavior of others. In the world of education, especially Islamic education, leadership in an Islamic educational institution has a strategic position in bringing Islamic educational institutions in the direction desired by a leader. Therefore, both the bad image of Islamic educational institutions is determined by both the poor performance, ability and image of a leader in managing the organization. In relation to the influence of the leadership of an Islamic educational institution-the head of a madrasah-, visionary leadership is needed as a requirement to create the effectiveness and efficiency of educational institutions, especially Madrasah Aliyah Negeri 2 Probolinggo, improving the quality of madrassas and forming the image of Islamic educational institutions. Keywords: Leadership Visionary and Organizational Culture